Methylphenidate and the risk of psychotic disorders and hallucinations in children and adolescents in a large health system - Man, K. K. C.; Banaschewski, Tobias (Translational Psychiatry, 2016)
Previous studies have suggested that risk of psychotic events may be increased in children exposed to methylphenidate (MPH). However, this risk has not been fully examined, and the possibility of confounding factors has not been excluded. Patients aged 6-19 years who received at least one MPH prescription were identified using Hong Kong population-based electronic medical records on the Clinical Data Analysis and Reporting System (2001-2014). Using the self-controlled case series design, relative incidence of psychotic events was calculated comparing periods when patients were exposed to MPH with non-exposed periods. Of 20,586 patients prescribed MPH, 103 had an incident psychotic event; 72 (69.9%) were male and 31 (30.1%) female. The mean age at commencement of observation was 6.95 years and the mean follow-up per participant was 10.16 years. On average, each participant was exposed to MPH for 2.17 years. The overall incidence of psychotic events during the MPH exposure period was 6.14 per 10,000 patient-years. No increased risk was found during MPH-exposed compared with non-exposed periods (incidence rate ratio (IRR) 1.02 (0.53-1.97)). However, an increased risk was found during the pre-exposure period (IRR 4.64 (2.17-9.92)). Results were consistent across all sensitivity analyses. This study does not support the hypothesis that MPH increases risk of incident psychotic events. It does indicate an increased risk of psychotic events before the first prescription of MPH, which may be because of an association between psychotic events and the behavioural and attentional symptoms that led to psychiatric assessment and initiation of MPH treatment.
Gesehen am 12.06.2019